Use of a SpermFilter - Alvarenga, Marco A. [UNESP]; Segabinazzi, Lorenzo G. T. M. [UNESP] (My University, 2021)
Sperm concentration is an important step for cryopreservation of stallion semen and a useful tool to improve sperm quality of cooled semen or of semen from subfertile stallions. The most common technique to concentrate sperm is centrifugation. In contrast, a SpermFilter is an effective alternative for sperm concentration. In addition, concentrating sperm using a SpermFilter also decreases bacterial contamination in the semen, since the sperm is retained in the filter, but the majority of bacteria flow through the filter with the supernatant. The SpermFilter consists in a synthetic hydrophilic membrane with 2 µl pores, which allows the flow of seminal plasma and extender through the membrane but retains the sperm.
Keywords: bacterial contamination; seminal plasma; sperm concentration; SpermFilter; stallion semen; subfertile stallions